Patient Satisfaction The Seger Waras Pratama Clinic in Polokarto Sukoharjo - Pujiyanto, Pujiyanto; Istiatin, Istiatin; Sudarwati, Sudarwati (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine the influence simultaneously (simultaneously) and partially of variablestherapeutic communication, service quality, brand image and trust in patient satisfaction at the Pratama Seger Waras Clinic in Polokarto Sukoharjo. This research method uses a quantitative research design. The population in this study were 863 patients at the Pratama Seger Waras Clinic in Polokarto Sukoharjo. The sampling technique used in this research was a purposive sampling technique with a sample size of 86 respondents. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that therapeutic communication, service quality, brand image and trust simultaneously and significantly influence patient satisfaction at the Pratama Seger Waras Clinic in Polokarto Sukoharjo. Suggestions from this research, Pratama Seger Waras Clinic in Polokarto Sukoharjo continues to improve therapeutic communication, service quality, brand image and existing trust, so that patient satisfaction will increase and be better than before.